Intensive Short-Term Dynamic Psychotherapy : Theory and Technique. - C., Della (Karnac Books, 2004)
This book is an accessible and comprehensive guide to the theory and practice of short-term treatment. It opens with a chapter on the theoretical foundations of the method before leading to its practical applications in clinical practice. It is highly recommended for all mental health professionals.